Assessment of the Region’s Energy Security Level in the Process of Formation of the Common European Energy Space - Pysar, Nadiia (International Journal of Energy Economics and Policy, 2019)
Creation of a single European energy space is impossible without proper and rapid assessment of the level of energy supply of the country. Depending on the specifics of regional development, indicators for assessing the level of energy security are different. Therefore, the study of the methodology for assessing the current state of the resource supply of the multifaceted energy system of the country is an important and topical task of the country’s management. The proposed methodology for an integrated assessment of the economic security level is characterized by the use of the multiplicative form of the integrated index and contains a number of additional recent indices; simultaneous normalization of indices and their threshold values by a common normalizing function; substantiation of the threshold value vector; as well as by a formalized definition of weighting factors, which allows to compare the dynamics of the integrated index with integrated threshold values on one scale, i.e. correctly identify the state of economic security. The theoretical approaches to the integrated assessment of the country’s energy security level have been analyzed and summarized and an evaluation methodology has been proposed that differs from the previous ones in that it allows to assess in detail the energy security level in the regional context. The paper describes the results of developing a methodology for assessing Ukraine’s energy security based on an indicative approach. The methodology for predicting threats to the country’s energy security has been provided. The numerical values and data sources of Ukraine’s energy security indices have been presented. Keywords: energy security, indicative analysis, threats, prediction, fuel and energy resources, modeling, assessment of the energy security level. JEL Classifications: O11; P28; R11; Q43 DOI: https://doi.org/10.32479/ijeep.7679